Analisis Pengaruh Pajak terhadap Peningkatan Pendapatan Asli Daerah di Kabupaten Tojo Una-Una - Taufik Bidullah (Universitas Batanghari Jambi, 2022)
Local taxes significantly influence local revenue to increase local revenue, and it is necessary to evaluate local revenue sources. The focus of this study is to ascertain how taxes affect local revenue in the Tojo Una-Una Regency. Data collection is done by using documentation techniques and a literature study. The variables used in this study are local revenue and local taxes. The data was then analyzed using a simple linear regression formula: correlation coefficient, determination coefficient, and statistical t-test using Minitab 19 software. The results showed that the simple regression coefficient value was 6.870, meaning that when taxes increased by one million, local revenue would increase by 6.870 million. The correlation value between local taxes and revenue is 0.976 (a very strong category). The obtained coefficient of determination has a value of 0.952, meaning that local taxes contribute 95.2% to the increase in local revenue. The results of the t-test, the calculated T value is 11.755 with a significance value of 0.000 < 0.01. So, there is a significant effect between local taxes on increasing local revenue in Tojo Una-Una Regency.